Basic researchEffect of feed supplementation with phytohaemagglutinin in combination with a-ketoglutarate on growth and nitrogen elimination pathways in rats with acute renal failure induced by nephrectomy - Filip, Rafał; Harrison, Adrian P.; Pierzynowski, Stefan G. (Archives of Medical Science, 2008)
Introduction: Phytohaemagglutinin (PHA) and alpha-ketoglutaric acid (AKG) in growing rats stimulate a change in the proportion of N excretion via urine and faeces, in favour of faecal excretion. The aim of the study was to investigate the effect of oral supplementation of PHA and AKG on pathways of nitrogen excretion and serum levels of urea in uraemic conditions induced by nephrectomy. Material and methods: Experiment 1 – 12 rats were assigned to one of two groups, control and PHA. Experiment 2 – PHA was administered to 36 male rats which were assigned to 4 groups: 1) uraemic control, 2) uraemic + AKG, 3) Sham-operated, 4) Sham-operated + AKG. AKG was administered via drinking water, while PHA was administered via a stomach tube. Results: Lower daily weight gain (P<0.05), increase in small intestine and total GI tract weight (P<0.05) as well as significant reduction in N excretion in urine in the PHA group were observed (P<0.05). Significantly higher daily weight loss in the uraemic rats, compared to that of the sham-operated rats, was observed (P<0.05). A significant increase in N excretion in faeces was observed in the AKG group, compared to control within the sham-operated rats (P<0.05) and when compared to the uraemic rats (P<0.05). In both sham-operated and uraemic rats, AKG treatment led to a significant reduction in the urea levels (P<0.05). Conclusions: The change in the proportion of N excretion via urine and faeces caused by PHA due to increasing the rate of protein production in the intestinal wall, apparently favouring faecal excretion, can be enhanced by the oral administration of AKG.